A study on the perception of IRB employees towards the E-Government implementation at their workplace / Nordianawaty Md Jali and Norizawati Perin - Md Jali, Nordianawaty; Perin, Norizawati (2011)
The objective of the study is to determine the perception of employee towards E-Government and to study the factors associated with perception towards E-Government implementation in Inland Revenue Board, Kota Kinabalu. The study was done at Inland Revenue Board, Kota Kinabalu. The respondent of the research were the employees of Inland Revenue Board. The result shows that there is an optimist good perception by the IRB employees towards the E-Government implementation in IRB and only the administrative support found out to have association with the employees' perception. It concluded that generally, the perception of the IRB employees toward E-Government application is at good perception. However, not all the dependent variable which had been determine as the factors associated with the employees' perception towards the e-government implementation in IRB found to be associated with the employees' perception.